TMSB4 Overexpression Enhances the Potency of Marrow Mesenchymal Stromal Cells for Myocardial Repair - Tang, Shiyuan; Fan, Chengming; Iroegbu, Chukwuemeka Daniel; Zhou, Wenwu; Zhang, Zhigong; Wu, Ming; Chen, Wangping; Wu, Xiaoming; Peng, Jun; Li, Zhihong; Yang, Jinfu (Frontiers in Cell and Developmental Biology, 2021)
Objective: The actin-sequestering proteins, thymosin beta-4 (Tβ4) and hypoxia-inducible factor (HIF)-1α, are known to be associated with angiogenesis after myocardial infarction (MI). Herein, we aimed to identify the mechanism of HIF-1α induction by Tβ4 and investigate the effects of bone marrow mesenchymal stromal cells (BMMSCs) transfected with the Tβ4 gene (TMSB4) in a rat model of MI. Methods: Rat BMMSCs were isolated, cultured, and transfected with the TMSB4 gene by using the lentivirus-mediated method. Rats with surgically induced MI were randomly divided into three groups (n=9/group); after 1 week, the rats were injected at the heart infarcted border zone with TMSB4-overexpressed BMMSCs (BMMSC-TMSB4OE), wild-type BMMSCs that expressed normal levels of TMSB4 (BMMSC-TMSB4WT), or medium (MI). The fourth group of animals (n=9) underwent all surgical procedures necessary for MI induction except for the ligation step (Sham). Four weeks after the injection, heart function was measured using transthoracic echocardiography. Infarct size was calculated by TTC staining, and collagen volume was measured by Masson staining. Angiogenesis in the infarcted heart area was evaluated by CD31 immunofluorescence histochemistry. In vitro experiments were carried out to observe the effect of exogenous Tβ4 on HIF-1α and explore the various possible mechanism(s). Results：In vivo experiments showed that vascular density 4 weeks after treatment was about two-fold higher in BMMSC-TMSB4OE-treated animals than in BMMSC-TMSB4WT-treated animals (p<0.05). The cardiac function and infarct size significantly improved in both cell-treatment groups compared to controls. Notably, the cardiac function and infarct size were most prominent in BMMSC-TMSB4OE-treated animals (both p<0.05). HIF-1α and phosphorylated HIF-1α (p-HIF-1α) in vitro were significantly enhanced by exogenous Tβ4, which was nonetheless blocked by the factor-inhibiting HIF (FIH) promoter (YC-1). The expression of prolyl hydroxylase domain proteins (PHD) was decreased upon treatment with Tβ4 and further decreased with the combined treatment of Tβ4 and FG-4497 (a specific PHD inhibitor). Conclusions: TMSB4-transfected BMMSCs might significantly improve recovery from myocardial ischemia and promote the generation of HIF-1α and p-HIF-1α via the AKT pathway, and inhibit the degradation of HIF-1α via the PHD and FIH pathways.